Modeling on oxide dependent 2DEG sheet charge density and threshold voltage in AlGaN/GaN MOSHEMT. (April 2016) - Panda, J.; Jena, K.; Swain, R.; Lenka, T. R.
Abstract: We have developed a physics based analytical model for the calculation of threshold voltage, two dimensional electron gas (2DEG) density and surface potential for AlGaN/GaN metal oxide semiconductor high electron mobility transistors (MOSHEMT). The developed model includes important parameters like polarization charge density at oxide/AlGaN and AlGaN/GaN interfaces, interfacial defect oxide charges and donor charges at the surface of the AlGaN barrier. The effects of two different gate oxides (Al2 O3 and HfO2 ) are compared for the performance evaluation of the proposed MOSHEMT. The MOSHEMTs with Al2 O3 dielectric have an advantage of significant increase in 2DEG up to 1.2 × 10 13 cm −2 with an increase in oxide thickness up to 10 nm as compared to HfO2 dielectric MOSHEMT. The surface potential for HfO2 based device decreases from 2 to −1.6 eV within 10 nm of oxide thickness whereas for the Al2 O3 based device a sharp transition of surface potential occurs from 2.8 to −8.3 eV. The variation in oxide thickness and gate metal work function of the proposed MOSHEMT shifts the threshold voltage from negative to positive realizing the enhanced mode operation. Further to validate the model, the device is simulated in Silvaco Technology Computer Aided Design (TCAD) showing good agreement with the proposed model results. The accuracy of the developed calculations of the proposed model can be used to develop a complete physics based 2DEG sheet charge density and threshold voltage model for GaN MOSHEMT devices for performance analysis.